Historical and current distribution and movement patterns of large herbivores in the Limpopo National Park, Mozambique - Roque, Dionísio Virgílio; Macandza, Valério António; Zeller, Ulrich; Starik, Nicole; Göttert, Thomas (Frontiers in Ecology and Evolution, 2022)
This study provides a first attempt to describe the historical distribution and movement patterns of selected large herbivore (LH) species in Limpopo National Park (LNP), an area in Mozambique today connected to a network of transboundary conservation areas. Between 1976 and the early 2000s, most LH species were absent in this area following the civil war in Mozambique during that time. Through the reconstruction of the historical and current distribution and movement patterns of seven LH species in five periods, we investigate possible changes in distribution and movement patterns over time. Data collection is based on a systematic literature search, censuses reports, online databases, dung count transects, and camera trap surveys. We mapped all LH observations and movements using ArcGIS 10.1. Our results reveal a dramatic collapse of LH populations between the peak of the colonial period and the post-colonial/civil war period (1800 – 2001), followed by a slight recovery from the post-proclamation of Great Limpopo Transfrontier Park to the current period (2002 – 2021). While LH population decline applied to all seven species, there are species-specific differences in the process of restoration: African elephant (Loxodonta africana), African buffalo (Syncerus caffer), and plains zebra (Equus quagga) appear to recover to a greater extent than giraffe (Giraffa camelopardalis), eland (Taurotragus oryx), blue wildebeest (Connochaetes taurinus) and white rhino (Ceratotherium simum). We found evidence of the functioning of proposed wildlife corridors in the LNP. The results give reason to assume that we are still in a very early and vulnerable state of restoration and that further efforts are necessary to strengthen the slowly increasing populations of LH. Our results highlight the importance of combining the past and current data as a guide for the restoration of threatened species in African savannas impacted by human activities.